System of public administration entities in times of war: the Ukrainian experience - Негара, Родіон Віталійович; Негара, Р. В.; Кальчук, Олексій Миколайович; Кальчук, Олексій Миколайович; Кальчук, О. М.; Kalchuk, Oleksii M.; Рябченко, Олена Петрівна; Рябченко, О. П.; Riabchenko, Olena P.; Капітанець, Світлана Володимирівна; Капітанець, С. В.; Kapitanets, Svitlana V.; et al. (Milan : CERIDAP of the University of Milan, 2025)
Il processo di istituzione della struttura della pubblica amministrazione in Ucraina è stato difficile e caratterizzato da una serie di riforme e riorganizzazioni. Ulteriori analisi sono necessarie per pervenire ad una comprensione completa dei modi in cui il sistema di amministrazione pubblica in Ucraina è stato modificata durante l’applicazione della legge marziale e al fine di valutarne la sua efficacia. L’obiettivo di questa indagine è di valutare le prestazioni dell’attuale sistema di amministrazione pubblica dell’Ucraina durante il conflitto, descrivere i cambiamenti rivoluzionari che la legge marziale ha portato, e esaminare lo stato attuale del sistema. Lo scritto individua le carenze nel funzionamento di specifiche organizzazioni della pubblica amministrazione e propone soluzioni per rimediare a tali carenze. The process of establishing the structure of public administration in Ukraine has been difficult, characterised by a series of reforms and reorganisations. Additional research is necessary to gain a comprehensive understanding of the ways in which the public administration system in Ukraine was modified during the operation of martial law and in order to evaluate its effectiveness. The objective of this investigation is to evaluate the performance of Ukraine's current public administration system during the conflict, describe the revolutionary changes that martial law has brought about, and examine the system's current state. The paper identifies shortcomings in the operation of specific public administration organizations and proposes solutions to address these deficiencies.
Nehara R. System of public administration entities in times of war: the Ukrainian experience / R. Nehara, O. Kalchuk, O. Riabchenko et al. // Ceridap. – Milan : CERIDAP of the University of Milan, 2025. - 2. - Р. 170–190. URL: https://doi.org/10.13130/2723-9195/2025-2-20
Keywords: система суб'єктів державного управління в Україні; ефективність чинної системи державного управління в Україні; воєнний стан; суб'єкти державного управління; system of public administration entities in Ukraine; effectiveness of the current system of public administration entities in Ukraine; martial law; entities of public administration